1996
DOI: 10.1016/0014-5793(96)00377-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of human caldecrin

Abstract: EcoRI tagged-mixed oligonucleotide primer pairs corresponding to Abstract Earlier we reported the primary structure of serum the caldecrin-specific sequence (encoding amino acids 63 69) and calcium-decreasing factor (caldecrin) from rat pancreas, a the elastase-conserved sequence (encoding amino acids 125 131) of protein which is considered to be a member of the elastase rat caldecrin. The amplified product of about 200 bp was cloned family. In this report, we describe the isolation of the two into pUCl9, sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…However, administration of procaldecrin did not decrease serum calcium levels [22] . Recombinant rat [11] and human [17] caldecrin also decreased serum calcium levels. In addition, rat protease activitydeficient caldecrin mutants (with His58Ala or Ser200Ala substitutions) decreased the levels of serum calcium.…”
Section: Activity Of Caldecrinmentioning
confidence: 89%
See 1 more Smart Citation
“…However, administration of procaldecrin did not decrease serum calcium levels [22] . Recombinant rat [11] and human [17] caldecrin also decreased serum calcium levels. In addition, rat protease activitydeficient caldecrin mutants (with His58Ala or Ser200Ala substitutions) decreased the levels of serum calcium.…”
Section: Activity Of Caldecrinmentioning
confidence: 89%
“…Caldecrin shows a greater similarity with elastase than with chymotrypsin. In addition, expressed recombinant human caldecrin also showed serum calcium-decreasing activity, even following phenylmethylsulfonyl fluoride treatment to abolish its protease activity [17] . In 1996, another research group purified a calcium metabolism-regulating factor from the porcine pancreas by determining its stimulatory effects on proliferation of the osteosarcoma MG-63 cell line and its inhibition of 1, 25 vitamin D3-stimulated calcium release in organ cultures [18] .…”
Section: Introductionmentioning
confidence: 98%
“…Five of these were reported in 2013 by a genetic study from Japan; variants p.R29Q, p.S239A, p.S239C, and p.K247E were found in individuals with chronic pancreatitis, whereas variant p.I209M was detected in a control subject (15). Variant p.R80W was identified during the cDNA cloning of human CTRC, described then as a "serum calcium decreasing protein," caldecrin, by Japanese authors in 1996 (25). Two novel variants were also included in the present study; variant p.R80Q was found in a pancreatic cDNA sample, whereas variant p.G214R was discovered in a subject with chronic pancreatitis in Slovakia.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on cDNA of human and rat chymotrypsinogen C have revealed that their predicted sequences are rather conserved, comprising a signal peptide of 16 residues and a mature form of 252 residues that includes 10 cysteine residues [11,12]. The zymogen form is activated by trypsin and cleaved into a small and a large peptide fragment linked by a disulfide bond [2].…”
Section: Introductionmentioning
confidence: 99%